Perancangan Aksesoris Ruang Interior dengan Menggunakan Penggabungan Material Utama Keramik dan Besi - Gunawan, Josephine Anastasia; Santosa, Adi; Pradjonggo, Celine Junica (Intra, 2018)
In this design, there are two material that has been used: ceramic and steel. Ceramic was originally from Greek: Keramikos, means a form of clay that has undergone the burning process. The most common ceramic’s characteristics are fragile and heavy. The other material is steel which has mechanical characters such as strength and ductility. Steel is easy to find, easy to process, relatively cheap, and also durable. Therefore, the designer designs interior accessories which combined both materials. Ceramic was choosen as the main material for this interior accessories because it easily formed. However, ceramic is fragile and not safe as a furniture material. Hence, the designer used ceramic as a decorative element to minimize the direct human contact. The design results are five sets of interior accessories. These accessories can prove that both material can be harmoniously combined and also proved that steel could reduce the weakness on ceramic material.